Analysis of the levels of tumour necrosis factor (TNF), autoantibodies to TNF, and soluble TNF receptors in patients with rheumatoid arthritis. (November 2013) - Lopatnikova, JA; Golikova, EA; Shkaruba, NS; Sizikov, AE; Sennikov, SV
Abstract : Objectives: To evaluate the potential contribution made by autoantibodies against tumour necrosis factor (TNF) to the pathogenesis of rheumatoid arthritis (RA). Method: We used affinity chromatography methods and a magnetic separation procedure to purify human autoantibodies specific to TNF. The autoantibodies were used as calibration material to determine the absolute content of autoantibodies to TNF using an enzyme-linked immunosorbent assay (ELISA). TNF content and the levels of soluble TNF receptors types I and II (sTNF-RI and sTNF-RII) were determined using commercial ELISA test kits. Results: We demonstrated significant increases in the levels of TNF, sTNF-RI, and sTNF-RII in the sera of patients with acute RA and in patients with RA who had responded positively to therapy compared with healthy controls. Levels of autoantibodies of the immunoglobulin (Ig)G2, IgG3, and IgG4 subclasses were significantly higher in sera from patients with acute RA than in sera from healthy controls. Level of autoantibodies of the IgG2 subclass were significantly higher in sera from patients with acute RA than in RA patients who had responded positively to therapy. Conclusions: Acute RA is associated with changes in levels of TNF and soluble receptors for TNF and also in levels of autoantibodies to TNF. Given the magnitude of the changes in levels of different subclasses of autoantibodies to TNF, we propose that these autoantibodies might contribute to the pathogenesis of RA.